Finite size effects on the structural and magnetic properties of sol-gel synthesized NiFe2O4 powders - George, M.; John, A. M.; Nair, S. S.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2006)
Nanoparticles of nickel ferrite have been synthesized by the sol-gel method and the effect of grain size oil its structural and magnetic properties have been Studied in detail. X-ray diffraction (XRD) studies revealed that all the samples are single phasic possessing the inverse spinel structure. Grain size of the sol-gel synthesized powders has been determined from the XRD data and the strain graph. A grain size of 9 nm was observed for the as prepared powders of NiFe2O4 obtained through the sol-gel method. It was also observed that strain was induced during the firing process. Magnetization measurements have been carried out on all the samples prepared in the present series. It was found that the specific magnetization of the nanosized NiFe2O4 powders was lower than that of the corresponding coarse-grained counterparts and decreased with a decrease in grain size. The coercivity of the sol-gel synthesized NiFe2O4 nanoparticles attained a maximum value when the grain size was 15 nm and then decreased as the grain size was increased further. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: grain size; magnetic properties; Nanoparticles; Nickel ferrite; strain

Finite size effects on the electrical properties of sol-gel synthesized CoFe2O4 powders: deviation from Maxwell-Wagner theory and evidence of surface polarization effects - George, Mathew; Nair, Swapna S.; Malini, K. A.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Physics D-Applied Physics, 2007)
Fine particles of cobalt ferrite were synthesized by the sol-gel method. Subsequent heat treatment at different temperatures yielded cobalt ferrites having different grain sizes. X-ray diffraction studies were carried out to elucidate the structure of all the samples. Dielectric permittivity and ac conductivity of all the samples were evaluated as a function of frequency, temperature and grain size. The variation of permittivity and ac conductivity with frequency reveals that the dispersion is due to Maxwell-Wagner type interfacial polarization in general, with a noted variation from the expected behaviour for the cold synthesized samples. High permittivity and conductivity for small grains were explained on the basis of the correlated barrier-hopping model.

Flexible microwave absorber based on nickel ferrite nanocomposite - Sunny, Vijutha; Kurian, Philip; Mohanan, P.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2010)
Flexible magnetic composite materials were prepared by incorporating precharacterized nickel ferrite nanoparticles in a natural rubber matrix. The complex dielectric permittivity and magnetic permeability of the composites were measured at different microwave frequencies using the cavity perturbation technique. A steady increase in dielectric permittivity was observed with increase in filler concentration. Maxwell-Garnett mixture equations were employed to model the effective permittivity and permeability of the composite. Reflection loss was estimated by employing the model of single layer absorber backed with a perfect conductor. Reflection loss minima of -5.9 dB at 3.2 GHz for 12 mm thick rubber ferrite composite sheet is obtained in the S-band while a loss up to -16 dB could be achieved at 9.5 GHz in the X-band. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cavity perturbation; Complex permeability; Complex permittivity; Microwave absorber; Nanocomposites; Nickel ferrite

Fluorescent superparamagnetic iron oxide core-shell nanoprobes for multimodal cellular imaging - Smitha, Sasidharan; Haseena, Vadakkenchery S.; Narayanan, Tharangattu N.; Mary, Antony P. Reena; Ajayan, Pulickel M.; Puthumana, Jayesh; Aziz, Anas A.; Aburto, Rebeca R.; Mani, Sendurai A.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Materials Express, 2012)
Multimodal imaging agents that combine magnetic and fluorescent imaging capabilities are desirable for the high spatial and temporal resolution. In the present work, we report the synthesis of multifunctional fluorescent ferrofluids using iron oxide as the magnetic core and rhodamine B as fluorochrome shell. The core-shell structure was designed in such a way that fluorescence quenching due to the inner magnetic core was minimized by an intermediate layer of silica. The intermediate passive layer of silica was realized by a novel method which involves the esterification reaction between the epoxy group of prehydrolysed 3-Glyidoxypropyltrimethoxysilane and the surfactant over iron oxide. The as-synthesized ferrofluids have a high saturation magnetization in the range of 62-65 emu/g and were found to emit light of wavelength 640 nm (lambda(excitation) = 446 nm). Time resolved life time decay analysis showed a bi-exponential decay pattern with an increase in the decay life time in the presence of intermediate silica layer. Cytotoxicity studies confirmed the cell viability of these materials. The in vitro MRI imaging illustrated a high contrast when these multimodal nano probes were employed and the R2 relaxivity of these sample was found to be 334 mM(-1)s(-1) which reveals its high potential as a T2 contrast enhancing agent.
Keywords: GPTMS; MRI Imaging; Multimodal Imaging; SPION; T2 Contrast Agent

Flexible microwave absorbers based on barium hexaferrite, carbon black, and nitrile rubber for 2-12 GHz applications - Vinayasree, S.; Soloman, M. A.; Sunny, Vijutha; Mohanan, P.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Applied Physics, 2014)
Flexile single layer electromagnetic wave absorbers were designed by incorporating appropriate amounts of carbon black in a nitrile butadiene rubber matrix along with an optimized amount of magnetic counterpart, namely, barium hexaferrite for applications in S, C, and X-bands. Effective dielectric permittivity and magnetic permeability were measured using cavity perturbation method in the frequency range of 2-12 GHz. The microwave absorbing characteristics of the composites were studied in the S, C, and X-bands employing a model in which an electromagnetic wave is incident normally on a metal terminated single layer. Reflection loss exceeding -20 dB is obtained for all the samples in a wide frequency range of 2-12 GHz when an appropriate absorber thickness between 5 and 9 mm is chosen. The impact of carbon black is clearly observed in the optimized composites on the mechanical strength, thickness, band width of absorption, dielectric properties, and absorptivity. (C) 2014 AIP Publishing LLC.